Microtus obscurus - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Microtus obscurus (Eversmann, 1841). Mem. Univ. Kazan, 156. TYPE LOCALITY: Siberia, Altai Mtns. DISTRIBUTION: Russia from the Crimea east through Siberia to the upper Yenesei River, south through NW Mongolia, NW China (Xinjiang), the Altai Mtns, Lake Balkash, to the Caucusus and N Iran (see Zagorodnyuk, 1991a). SYNONYMS: brevirostris, gudauricus, ilaeus, ileos, innae, iphigeniae, macrocranius, transcaucasicus, transuralensis. COMMENTS: Subgenus Microtus, arvalis species group sensu Zagorodnyuk (1990). Formerly included in M. arvalis (e.g., Corbet, 1978c) but shown to be a distinct species by Zagorodnyuk (1991a, b) based on morphological and chromosomal features. The species appears to be parapatric with M. arvalis (Zagorodnyuk, 1991a). Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 526, DOI: 10.5281/zenodo.7353098